EKSPERIMENTASI MODEL PEMBELAJARAN NESTED DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN KONTEKSTUAL PADA MATERI POKOK BANGUN RUANG SISI DATAR DITINJAU DARI KECEMASAN BELAJAR MATEMATIKA SISWA KELAS VIII MTs PONOROGO TAHUN PELAJARAN 2013/2014 - Rivia J, Hefin Dwi; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this study were to know: (1) which one gave students a better learning achievement, Nested learning model and Think Pair Share with Contextual, or Direct Instruction, (2) which one has better learning achievement in mathematics, students who have the level of low anxiety, medium one, or high one. (3) which level of anxiety in learning mathematics gave better learning achievements using Nested learning model and Think Pair Share with Contextual approach, or Direct Instruction, (4) which learning model (Nested and Think Pair Share with Contextual approach, or Direct Instruction) gave better learning achievement in mathematics toward students with high, medium or low anxiety. It was a quasi-experimental study using two independent variables (model of learning and the anxiety of learning mathematics) and one dependent variable (learning achievement of mathematics). The instruments used to collect the data were documentation, testing, and questionnaires. Two-way ANOVA with unequal cell was used to analyze the data. The sample-taking was done using Stratified Cluster Random Sampling. The results of the research were: (1) the learning achievement in Nested learning model is better than learning achievement in Think Pair Share learning model and Direct Instruction, the learning achievement in Think Pair Share learning model is better than Direct Instruction one, (2) students with low anxiety have better learning achievement in mathematics than students with medium and high anxiety, and the ones having medium anxiety have better learning achievement in mathematics than the ones with high anxiety, (3) in Nested, Think Pair Share, and Direct Instruction learning model, the learning achievement in mathematics toward low anxiety students is better than medium and high anxiety students and medium anxiety students learning is better than high anxiety, and (4) in low, medium, and high anxiety students, the learning achievement in Nested learning model is better than Think Pair Share model and Direct Instruction, Think Pair Share model is better than Direct Instruction one.Keywords: Nested, Think Pair Share, Direct Instruction, Anxiety.